EFEKTIVITAS EKSTRAK DAUN SIRIH DALAM MENANGGULANGI IKAN PATIN YANG TERINFEKSI BAKTERI Aeromonas hydrophila - Dini Siswani Mulia; Arif Husin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2012)
This study aimed to assess the effectiveness in dealing with betel leaf extract catfish infected with Aeromonas hydrophila. This study used an experimental method to completely randomized design (CRD) with 4 treatments and 4 replications. Treatment consists of feed pellets P1 = + 0.2 g of betel leaf extract / 100 g feed; P2: feed pellets + 0.4 g of betel leaf extract / 100 g feed, P3: feed pellets + 0.6 g of betel leaf extract / 100 g of feed, and P4: feed pellets without betel leaf extract (control). Catfish used a length of 7.8 to 11.3 cm with an average weight of 7.43 g. Feed containing betel leaf extract made after the onset of symptoms of fish to bacteria A. hydrophila, namely on day 3 to day 18 (for 15 days). Parameters be measured were survival rate, clinical symptoms (external) fish, and the process of recovery (recovery) of catfish after bacterial infection A. hydrophila, as well as water quality parameters, including temperature, pH, and dissolved oxygen. Analysis of data using Analysis of Variance (ANOVA) and Duncan's test further with Multiple Range Test (DMRT) at 5% level test. The results showed that the betel leaf extract effective in preventing bacterial infection catfish A. hydrophila. Treatment of betel leaf extract may improve survival catfish reaches 66.67 to 86.11% compared to 30.55% for controls. P1 treatment is the most effective treatment for treating bacterial infections catfish A. hydrophila. Keywords: effectiveness, betel leaf extract, catfish, infection, Aeromonas